PENGARUH PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN DAN KOMPETENSI TERHADAP KINERJA MANAJERIAL - Prisca Patricia Liem (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2022)
The purpose of this study is to look at the effect of applying accountability accounting and competence to the managerial performance of PT. Pegadaian (Persero) Kanwil V Manado. Sampling technique that used in this study is non probability sampling with purposive sampling method and data collection was carried out using a questionnaire. The amount of sample in this study are 57 sample. The analysis technique is multiple linear regression. The results of this study indicate that accountability accounting and competence have a positive and significant effect on the managerial performance of PT. Pegadaian (Persero) Kanwil V Manado.